Machine translation and the L2 classroom: Pedagogical solutions for making peace with Google translate - Ducar, Cynthia; Schocket, Deborah Houk (Foreign language annals, 2018)
This article addresses a key pedagogical issue of our time: the widespread yet generally unwelcome presence of machine translation (MT) in the language classroom. Studies have repeatedly shown that L2 students consult the most widely used translation tool, Google Translate (GT), in spite of the fact that its use is frowned upon by second language (L2) instructors. Even so, academic honesty violations are not always reported, nor is there a consensus on whether the use of MT constitutes a form of cheating. Recognizing the omnipresence of GT in L2 student work, this article examines current research on the use of MT, highlights the strengths and limitations of this technology, explores 21st‐century pedagogical solutions designed to harness the capabilities of both MT and alternative technologies, and suggests venues for future research with the goal of ensuring learners’ academic growth in line with ACTFL's Can‐Do Statements for Intercultural Communication. The Challenge Google Translate (GT) is an inescapable reality in today's second language (L2) classroom. What challenges and opportunities does this technology present to L2 students and instructors? Is it possible to deter students from overusing this technology? How can teaching students about the strengths and weaknesses of this technology transform some of the challenges into learning opportunities?